British Management and Strategic Change - Pettigrew, A; Thomson, A; Rubashow, N (1985)
The anatomy of strategic change in companies in Europe has been little investigated. Recently the British Economic and Social Research Council sponsored an audit of management based on interviews with over 1000 middle and senior executives and directors in 190 companies. The survey examined the origins and correlates of change and found that based on the perceptions of the managers, an orientation towards change in its various dimensions was most closely correlated with companies which had explicit management development programmes.